Lead and cadmium in soils of La Rioja vineyards Spain - Marín, Álvaro; Andrades, Marisol; Iñigo, Victoria; Jiménez-Ballesta, Raimundo (Land Degradation and Developement, 2017)
Land degradation can be triggered by the abuse of chemicals that damage soil quality. Agriculture is changing the chemical and physical properties of soils, and in vineyards, those changes are due to the use of pesticides. In order to assess the Pb and Cd content, 212 soil samples from La Rioja D. O. Ca were analysed. Concentrations of Pb in soil ranged from 0.96 to 64.31 mg kg(-1) with a mean concentration of 21.26 mg kg(-1) in the surface layer, while they ranged from 7.97-43.93 mg kg(-1) with a mean of 20.83 mg kg(-1) in the subsurface layer. The mean content of bioavailable lead was 1.03 mg kg(-1) in the surface layer and 0.76 mg kg(-1) in the subsurface. Cd overall average concentration was 0.29 mg kg(-1) in the surface; in the subsurface, the mean was 0.31 mg kg(-1) and ranged from 0.10 to 1.22 mg kg(-1). The values in the surface layers were 0.15 mg kg(-1) and in the subsurface layer 0.01 of Cd bioavailability. On the basis of pedogeochemical Pb and Cd distribution, balanced fertilization will be of great importance for sustainable development of agricultural wine-producers.
Keywords: lead and cadmium; vineyard soils; guideline levels; spatial variability; La Rioja DOCa; JCR; Scopus